Statistical Analysis Of The Index Of Economic Freedom 2017 Improve The Sequence Of Countries Through Policy Priorities IraqAsAModel - Karim Jassim, Ahmed; M. Queen, Abdulkadim (Opción, 2019)
The Freedom Foundation’s Institute for Economic Freedom publishes the Economic Freedom reform, a ranking or ranking of 180 countries or semi-au- tonomous territories, as well as 6 non-classified countries, ending the list ranked 180th in North Korea with an index 4.9. It is regrettable that North Korea follows Iraq as the first unrated country to be followed by five countries including four Arab countries namely Libya, Somalia, Syria and Yemen, all of which are outside the classification, Therefore research study is a study of the index of economic freedom of 2017 focusing attention on Iraq, which can im- prove the location of Iraq In the ranking by a change in policy priorities. Two important indicators were identified for achieving the goal: Financial Free- dom and Trade Freedom, followed by the importance of Judicial Efficiency, Investment freedom, and so on.